Borehole imaging : applications and case histories - Lovell, M. A., 1955-; Williamson, Gail; Harvey, P. K. (Geological Society special publication, 1999)
Borehole images now form a major part of the interpretation strategy for subsurface geological interpretation in a wide variety of scenarios. This volume documents some case histories together with image acquisition and analysis techniques, and includes three major reviews of recent applications and technical developments. The contributions begin with an introduction and review on the technology and applications of the subject, which also includes a sustantial bibliography detailing many of the relevant research papers. A timely and necessary appraisal of the fundamentals of electrical and ultrasonic borehole imaging tools and processing methods forms a second review in this collection. Anyone utilizing borehole images will benefit from studying the third review paper on the recognition of artefacts in these images. The wealth of case histories of borehole imaging in the remainder of this volume provides an up to date glimpse of the wide range of applications and uses.